Empowering Higher Education: The Tech Advantage in Work Coordination and Risk Management for Financial Growth - Rauf, Ummu Ajirah Rauf; Ahmed, Saif; Deli, Mazzlida Mat; Asha’ari, Maryam Jamilah; Jamil, ‘Ainul Huda; Abdullah, Mohd Hafizuddin Syah Bangaan; Abdullah, Siti Intan Nurdiana Wong (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study examined the relationship of work coordination and Enterprise Risk Management on financial performance in Malaysian public higher education (PHEs). It addresses the gaps on how work coordination and ERM could mitigate financial challenges such as dependence on tuition fees and limited government funding. The responses from 350 key informants across 20 Malaysian PHEs were analyzed using SEM analysis. The findings reveal that work coordination significantly enhances ERM implementation, and ERM implementation positively influence the financial performance, ERM also act as a mediator variable, which has a greater effect on financial performance through work coordination. The findings support the strategic role of ERM in facilitating links between organizational capabilities and financial sustainability. It thus practically recommends increasing capacity through governance structures, investing in digital tools for risk management, and engaging leaders to improve ERM effectiveness. Theoretically, this study extends the Resource-Based View, placing ERM as that critical resource that would turn coordinated efforts into measurable financial outcomes. This study closes the literature gap in risk management in higher education by integrating work coordination and ERM within a comprehensive model of financial sustainability that has pragmatic implications for policymakers and leaders of institutions in strengthening resilience within resource-constrained educational contexts.